2015
DOI: 10.1371/journal.pone.0121372
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Positive Effect’ Is Present in Older Chinese Adults: Evidence from an Eye Tracking Study

Abstract: The 'Positive Effect' is defined as the phenomenon of preferential cognitive processing of positive affective information, and avoidance or dismissal of negative affective information in the social environment. The ‘Positive Effect’ is found for older people compared with younger people in western societies and is believed to reflect a preference for positive emotional regulation in older adults. It is not known whether such an effect is Universal, and in East Asian cultures, there is a highly controversial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…For instance, Mather and Carstensen (2005) in a review article found that as people get older, they experience fewer negative emotions. The same positive emotion effect has been found in Chinese older adults from an eye-tracking study (Wang, He, & Jia et al, 2015). Older adults show more emotionally gratifying memory distortion for post choices and autobiographical information than younger adults do.…”
Section: Attitude Toward Ageingsupporting
confidence: 69%
“…For instance, Mather and Carstensen (2005) in a review article found that as people get older, they experience fewer negative emotions. The same positive emotion effect has been found in Chinese older adults from an eye-tracking study (Wang, He, & Jia et al, 2015). Older adults show more emotionally gratifying memory distortion for post choices and autobiographical information than younger adults do.…”
Section: Attitude Toward Ageingsupporting
confidence: 69%
“…The age-related positivity effect, which was quite commonly found in the US (see Scheibe & Carstensen, 2010 for a review) was replicated in East Asian cultures in some studies (e.g., Chung & Lin, 2012;Gong et al, 2014;Ko et al, 2011;Kwon et al, 2009;Wang et al, 2015;Zhang et al, 2016), but not others (Fung et al, 2008;Fung & Tang, 2005 with younger adults. These results are consistent with prior findings that there is an age-related positivity effect on gaze preference among US Americans (e.g., Isaacowitz et al, 2006), but no such effect, or even a reverse effect, among Hong Kong Chinese (e.g., Fung et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…When Korean participants were compared to US participants, Korean older adults show a similar age-related positivity effect to US older adults in memory tasks (Kwon et al, 2009 ; Ko et al, 2011 ). A recent study also reveals that Chinese older adults demonstrate larger preferences toward positive stimuli in attention (Wang et al, 2015 ) as observed in US older adults (Knight et al, 2007 ).…”
Section: Introductionmentioning
confidence: 77%